Assessment of research productivity in the foreign library science as a part of measuring the library effectiveness - P. S. Romanov (Библиосфера)
The article evaluates data bases and other sources of information, as well as research methods used to rank the research productivity of library scientists and lecturers of library and information technology faculties in the USA. Tools and methods are identified to study high accurate ranking of research productivity or publication activity of library scientists and teachers of library higher schools.